Malate-Dependent Carbon Utilization Enhances Central Metabolism and Contributes to Biological Fitness of Laribacter hongkongensis via CRP Regulation - Xiong, Lifeng; Chan, Elaine; Teng, Jade L. L.; Liu, Siguo; Lau, Susanna K. P.; Woo, Patrick C. Y. (Frontiers in Microbiology, 2019)
Metabolic adaptation in various environmental niches is crucial for bacterial extracellular survival and intracellular replication during infection. However, the metabolism of carbon/nitrogen sources and related regulatory mechanisms in Laribacter hongkongensis, an asaccharolytic bacterium associated with invasive infections and gastroenteritis, are still unknown. In present study, we demonstrated that malate can be exploited as preferred carbon source of L. hongkongensis. Using RNA-sequencing, we compared the transcriptional profiles of L. hongkongensis cultivated with/without malate supplementation, and observed that malate utilization significantly inhibits the use of alternative carbon sources while enhancing respiratory chain as well as central carbon, sulfur and urease-mediated nitrogen metabolisms. The tight connection among these important metabolic pathways indicates that L. hongkongensis is capable of integrating information from different metabolism branches to coordinate the expression of metabolic genes and thereby adapt to environmental changing. Furthermore, we identified that a transcription factor, CRP, is repressed by malate-mediated metabolism while negatively regulating the effect of malate on these central metabolic pathways. Remarkably, CRP also responds to various environmental stresses, influences the expression of other transcription factors, and contributes to the biological fitness of L. hongkongensis. The regulatory network and cross-regulation enables the bacteria to make the appropriate metabolic responses and environmental adaptation.